Dampak Media Subkultur dan Variasi Subkultur untuk Pertumbuhan Tunas pada Kultur Jaringan Pisang (Musa spp.) Serta Penerapan Penanaman Bibit Dengan Pemberian Agen Hayati - Era Maulia; Wika Rahmatika; Mizan Maulana (Yayasan Perguruan Kampus, 2025)
This study aims to evaluate the impact of subculture media on shoot proliferation in banana (Musa spp.) tissue culture. The experiment was conducted using Murashige & Skoog (MS) medium and a modified medium, with subculture variations of 2, 4, and 6 cycles. The observed parameters included the number of shoots, shoot height, root count, and root length. Results showed that shoot and root growth in the modified medium with activated charcoal and four subculture cycles produced the best shoot proliferation response compared to other treatments. The combination of culture media and subculture frequency significantly enhances propagation efficiency in sustainable elite seedling production. This strategy offers an innovative solution for modern agriculture, addressing efficiency challenges amid production instability, climate change threats, and land degradation.